ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM KEPUTUSAN MENGGUNAKAN LISTRIK PRABAYAR (Studi Pada Warga Perum Pepabri Keniten Kabupaten Ponorogo) - AMELINDA EKASARI, KARIN (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Marketing has the aim of meeting the needs, desires, and expectations of consumers. It is expectations of consumers. It is expected that by studying the behaviour of consumers, businessmen are able to know the needs, desires and expectations of the target consumers so as to give satisfaction to their costumers. This study was conducted to determine the factors that influence consumer behaviour in the decision to use prepaid electricity. This study used observation, questionnaires, literature study and internet access. Questionnaire included 82 customers PLN in Housing Pepabri Keniten Ponorogo. The test using factor analysis which aims to find the dominant factor. While the techniques of data analysis using factor analysis. Characteristics of respondents surveyed include: a description of the respondents think since when using prepaid electricity, according to the description of the age, description of respondents by sex. While the most dominant factor is the price factor with a value of 88,30% of the total variance. Keywords : Factor analysis, purchase decision, prepaid electricity